1992
DOI: 10.3758/bf03200409
|View full text |Cite
|
Sign up to set email alerts
|

Comparing spatial memory in two species of tit: Recalling a single positive location

Abstract: The performance of a food-storing species, the marsh tit tParue palustris), was compared with that of a nonstorer, the blue tit (P. caeruleusi, in a spatial memory task in which birds had to return to a site where they had previously been allowed to eat part of a piece ofpeanut. No differences were found between species' overall performance, but increasing retention interval from 1 min to 24 h brought about a decrease in performance. The results are discussed in relationship to the hypothesis that food-storing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…The data suggested (the effect was just short of significance) that the two foodhoarding species' reduction in performance with increasing retention interval (up to 24 h) was shallower (and therefore memory duration longer lasting) than that of the two non-hoarding species. However, studies using a one-trial associative memory design that had a range of retention intervals up to 24 h did not find any evidence (or even non-significant trends) of better performance of food-hoarding tits at the longer retention intervals (Healy & Krebs 1992a;Clayton & Krebs 1993). No studies to date have compared memory duration between hoarding and non-hoarding tits at intervals longer than 24 h though, so the jury remains out on whether having a one-trial memory duration of several weeks is an adaptive specialization of food-hoarding tits or not.…”
Section: Using Ecology To Predict Specific Memory Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data suggested (the effect was just short of significance) that the two foodhoarding species' reduction in performance with increasing retention interval (up to 24 h) was shallower (and therefore memory duration longer lasting) than that of the two non-hoarding species. However, studies using a one-trial associative memory design that had a range of retention intervals up to 24 h did not find any evidence (or even non-significant trends) of better performance of food-hoarding tits at the longer retention intervals (Healy & Krebs 1992a;Clayton & Krebs 1993). No studies to date have compared memory duration between hoarding and non-hoarding tits at intervals longer than 24 h though, so the jury remains out on whether having a one-trial memory duration of several weeks is an adaptive specialization of food-hoarding tits or not.…”
Section: Using Ecology To Predict Specific Memory Adaptationsmentioning
confidence: 99%
“…The third prediction was that memory spatial resolution should be better in hoarding than in non-hoarding species. Studies using the same one-trial associative memory task as mentioned above have sometimes (Clayton & Krebs 1993), but not always (Healy & Krebs 1992a;Clayton & Krebs 1994a), shown species differences in the number of mistakes made. Food-hoarding species seem to remember where they have found food, whereas non-hoarding species only seem to remember where they have been (Clayton & Krebs 1994b).…”
Section: Using Ecology To Predict Specific Memory Adaptationsmentioning
confidence: 99%
“…Healy and Krebs (1992) found no difference between marsh tits and blue tits-storing and nonstoring members, respectively, of the parid family-on their ability to retain the location of a single site associated with reinforcement, although performance did approach chance levels as the retention interval approached 24 h. Healy and Krebs suggested that.differences might only be detected if the ability to recall multiple sites was tested. Although there is obviously a difference between recalling the location oftwo sites and recalling the location of hundreds of sites, our results nevertheless demonstrate that pigeons can recall more than a single spatiallocation-food association.…”
Section: Resultsmentioning
confidence: 99%
“…However, in Experiment 1, our subjects were required to recall only a single positive location (see Healy & Krebs, 1992, for an experiment comparing a storing and a nonstoring species on their ability to recall a single positive location). In the wild, food-storing birds are thought to recall the location of numerous different cache sites, and the possibility exists that differences in spatial memory performance on this type of task would only be detected when subjects are required to recall multiple sites.…”
Section: Methodsmentioning
confidence: 99%
“…What is important about the knowledge of Equation 3 is that we can test inferences about the expected number of successes out of n sites searched using a Z test rather than a t test, as is commonly employed (e.g., Healy & Krebs, 1992;Hilton & Krebs, 1990;Olton & Samuelson, 1976;Spetch & Edwards, 1986). This is important since the Z test is more powerful (i.e., better able to reject a false null hypothesis) than the t test.…”
mentioning
confidence: 99%